Green chemistry approaches for extraction of cellulose nanofibers (CNFs): A comparison of mineral and organic acids. (2022) - Mhlongo, Jessica Tsakani; Nuapia, Yannick; Motsa, Machawe Mxolisi; Mahlangu, Themba Oranso; Etale, Anita
Abstract: This study reports for the first time an environmentally friendly process to prepare cellulose nanofibrils (CNFs) from industrial Hemp ( Cannabis sativa L. ) bast fibers by acid hydrolysis treatment combined with ultrasonication. Hemp bast fibers were pretreated using 4 wt% NaOH (alkali treatment) followed by bleaching with acetate buffer in aqueous chlorite. The morphology, chemical functional groups, thermal stability, and crystallinity of the nanocellulose nanofibers were obtained via characterization using scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) analysis and thermogravimetric analysis (TGA). FTIR spectra revealed that no new chemical functional groups were introduced on the surface of cellulose nanofibers when compared to bleached cellulose. XRD data and SEM micrographs showed that low sulfuric acid hydrolysis led to higher crystalline and rod-like cellulose nanofibers, whereas hydrolysis at higher concentration of sulfuric acid resulted in lower crystalline cellulose nanofibers. Cellulose nanofibers with high crystallinity also had good thermal stability, which is a favourable property for high temperature applications. Based on the findings, it was concluded that low-cost hemp bast fiber can be regarded as a greener and sustainable industrial waste for the preparation of cellulose nanofibers with superior crystallinity and thermal stability.